2019
DOI: 10.1096/fj.201901624rr
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel proteolytically inactive mutations in coronavirus 3C‐like protease using a combined approach

Abstract: Coronaviruses (CoVs) infect humans and multiple other animal species, causing highly prevalent and severe diseases. 3C-like proteases (3CL pro s) from CoVs (also called main proteases) are essential for viral replication and are also involved in polyprotein cleavage and immune regulation, making them attractive and effective targets for the development of antiviral drugs. Herein, the 3CL pro from the porcine epidemic diarrhea virus, an enteropathogenic CoV, was used as a model to identify novel crucial residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 59 publications
0
51
0
1
Order By: Relevance
“…The known coronavirus 3-chymotrypsin-like protease (3CLpro), also known as Mpro, is the main protease, which is required for proteolytic maturation of the corona virus. This Mpro have an essential role in the immune regulation and cleaving the polyproteins pp1a and pp1ab, which making them attractive and important targets for anti-COVID-19 drugs (Zhou et al, 2019). Functional proteins such as RNA polymerase, endoribonuclease and exoribonuclease are generated by cleavage of pp1a and pp1ab polyproteins by Mpro .…”
Section: Introductionmentioning
confidence: 99%
“…The known coronavirus 3-chymotrypsin-like protease (3CLpro), also known as Mpro, is the main protease, which is required for proteolytic maturation of the corona virus. This Mpro have an essential role in the immune regulation and cleaving the polyproteins pp1a and pp1ab, which making them attractive and important targets for anti-COVID-19 drugs (Zhou et al, 2019). Functional proteins such as RNA polymerase, endoribonuclease and exoribonuclease are generated by cleavage of pp1a and pp1ab polyproteins by Mpro .…”
Section: Introductionmentioning
confidence: 99%
“…3CLpro and PLpro are encoded by ORF-1 of virus genome which plays a major role in the processing of inactive polyproteins (pp1a and pp1ab) into active non-structural proteins (nsps). These nsps finally helps in the replication, generation, as well as infection of the virus (Zhou et al., 2019 ). Inhibition of these proteases can be crucial for further replication and infection of SARS-CoV2 (Wu et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bananin (BN) effectively suppresses both SARS-CoV RNA/DNA helicase nucleic acid unwinding function and SARS-CoV RNA-viral replication in cell culture [72]. In addition, high-throughput screening (HTS) approaches were used to screen potent inhibitors of the SARS-CoV main proteinase [73,74]. Recent computational studies found that lopinavir, oseltamivir and ritonavir are able to bind with SARS-CoV-2 protease [75].…”
Section: Pharmacological Therapeutics Targeting Proteinase Of Sars-cov-2mentioning
confidence: 99%